A conceptual synthesis of organisational transformation: How to diagnose, and navigate, pathways for sustainability at universities?. (1st March 2017) - Baker-Shelley, Alex; van Zeijl-Rozema, Annemarie; Martens, Pim
Abstract: Universities will play a profound role in a century in which society will be judged by its capacity for self-transformation in response to pandemic crises of climate change and capitalism. Frameworks of analysis of sustainability in organisations could benefit from tangible systemic rubrics for transformation. This research delineates core elements of organisational transformations for sustainability at universities. Criteria were woven into a framework that has value as a diagnostic tool, spanning three scales and five theoretical perspectives: behavioural science, corporate governance and responsibility, organisational change management, socio-ecological systems and sustainability in education and research. This was geared towards what organisational transformation for sustainability entails with universities specifically, if leverage points can be identified, and what the moral imperatives are of universities pursuing sustainability transformation. The orientation was to deduce distinct 'rules of the game' to diagnose organisational transformations for sustainability through descriptive and prescriptive criteria. The findings suggest high capacity for organisational transformation involves extroverted engagement, where potential rubrics help standardise comparison of environmental social governance issues in similar cultural and regional contexts. Students, academics, researchers and practitioners co-create knowledge in a 'republic of stakeholders', through a dialogical process of organisational-societal learning. Internally, an integrated approach, cross-linking information and disciplines from a network of actors has benefits for psychological wellbeing. Criteria for diagnosis could be formulated into an instrument through testing the analytical framework in transdisciplinary research cases. Future research might well focus on institutional differentiation and evolution of public research universities that navigate departures from traditional models, co-creating in reflexive iterations to achieve leverage for sustainability transformation.